An Evaluation of the Master of Arts Degree Programe in Moral Theology updated 2019, Faculty of Divinity of Saengtham College. - Sugiyo Pitoyo, Agustinus; Lertjitlekha, Cherdchai; Suksamran, Nantapon; Le Duc, Anthony; Chumsriphun, Rev.Dr.Surachai; Saengthien, Rev.Dr.Pichet; Pongsiri, Chartchai; Pittayaphongphon, Somchai; Prasootsaengchan, Kriengsak; Prasootsaengchan, Laddawan (Saengtham College Journal, 2024)
This study was aimed: 1) to evaluate the Master of Arts Degree Programe in Moral Theology updated 2019, Faculty of Divinity of Saengtham College focusing on context, input factors, process and product of the program, and 2) to study needs to improve the program as regarded by stakeholders of this study comprised 51 respondents, including 2 administrators, 10 instructors, 16 students, 19graduates and 6 graduates’ employers. The research instruments was a set of opinionnaires. The collected data were analyzed by percentage (%), mean ( ), standard deviation (S.D.) and content analysis. The results of the study were as follows : 1) The Evaluation of program as a whote was appropriate at the highest level with less data dispession ( = 4.57, S.D. = 0.514). As taken a careful consideration, it revealed that all aspects were at the highest except the output which was at a high level. 2) The Stakeholders regarded that all aspects of the program were needed for improvement.